Komitmen dan Kapabilitas Penyelenggara Pemerintahan Nagari dalam Operasionalisasi Tugas Pokok dan Fungsinya di Sumatera Barat - Lanin, Dasman (Jurnal Demokrasi, 2003)
This research aimed at describing the commitments of â€œNagariâ€ Government officers all the province of West Sumatera in carrying out their main duties and their capabilities, either in the bodies of Legislative or Executive, Religious Consideration, and Conservation of Local Culture/Custom.Â Â  For this purpose qualitative approach was used through â€œmean and percentageâ€ analysis.Â  The finding of this research indicated that the commitment of the â€œNagariâ€ Government officers is not too different from their capabilities. A few of the commitments and capabilities tend to be in high grades or categories, while most of them tend to be in low grades or categories. Kata Kunci: Commitment and capability, penyeleng-gara pemerintahan, tugas pokok dan fungsi